Childhood trauma exposure in substance use disorder patients with and without ADHD. (February 2017) - Konstenius, Maija; Leifman, Anders; van Emmerik-van Oortmerssen, Katelijne; van de Glind, Geurt; Franck, Johan; Moggi, Franz; Ramos-Quiroga, Josep Antoni; Levin, Frances R; Carpentier, Pieter Jan; Skutle, Arvid; Bu, Eli-Torild; Kaye, Sharlene; et al.
Abstract: Background: Childhood trauma exposure (CTE) is frequently reported by those with substance use disorders (SUDs). SUDs also frequently co-occur with attention deficit hyperactivity disorder (ADHD). Objective: To investigate the role of childhood trauma exposure (CTE) in the presence and the persistence of ADHD in treatment seeking SUD patients. Method: Data was derived from the International ADHD in Substance Use Disorder Prevalence (IASP) study. A structured interview was administered to 1274 treatment-seeking SUD patients aged 18 to 65. Results: CTE was present in 53.5% of the patients and comorbid adult ADHD in 14.1%. CTE was significantly associated with ADHD: the prevalence of adult ADHD with and without CTE was 19.4% and 8.5% (OR adjusted for age, gender, main substance of abuse, BPD, and ASPD 1.91 [95% CI 1.29–2.81]). CTE was not associated with the severity of adult ADHD or with the persistence of childhood ADHD into adulthood. Conclusions: CTE is common in SUD patients and associated with adult ADHD but not with the persistence of childhood ADHD into adulthood. These findings suggest that the increased rate of adult ADHD in SUD patients with CTE is not the consequence of a negative effect of CTE on the persistence of childhood ADHD into adulthood, but a direct expression of the high rate of childhood ADHD in SUD patients with CTE. Highlights: CTE was more frequent in adult treatment seeking SUD patients with comorbid ADHD compared to those without ADHD. CTE was not associated with severity of ADHD symptoms. CTE did dot effect the persistence of ADHD into adulthood.